Observing variable stars novae and supernovae - North, Gerald (New York, Cambridge University Press, 2004)
Variable stars can be fascinating objects to study. This complete practical guide and resource package instructs amateur astronomers in observing and monitoring variable stars and other objects of variable brightness. Descriptions of the objects are accompanied by explanations of the background astrophysics, providing readers with a real insight into what they are observing at the telescope. The main instrumental requirements for observing and estimating the brightness of objects by visual means and by CCD photometry are detailed, and there is advice on the selection of equipment. The book contains a CD-ROM packed with resources, including hundreds of light-curves and over 600 printable finder charts. Containing extensive practical advice, this comprehensive guide is an invaluable resource for amateur astronomers of all levels, from complete beginners to more advanced observers.
Glossary 211-216p.; Index 221-230p.
Keywords: Novae; Supernovae; Stars; Variable stars; Physics